L’écriture et « La forêt » - Schoentjes, Pierre (Verbum – Analecta Neolatina, 2012)
Starting from a close reading of La forêt (in : Le règne végétal, 1981) by much praised but alas long forgotten Gallimard author Pierre Gascar, this study aims to demonstrate how nature-writing influences the way we consider nature in our ecological-conscious world. Using intuitions expressed by Fowles in his seminal The Three (1979), this ecopoetic reading echoes a series of important writers, from Mario Rigoni Stern to Claude Simon over other major contemporary writers.